Estimating decay heat removal rate by natural convection for Tehran Research Reactor - farhadi, Kazem (Progress in nuclear energy (New series), 2012)
An integral boundary layer model is developed in that both the Boussinesq and non-Boussinesq approximations are taken into consideration. The model analyzes laminar free convection between nuclear fuel plates having large aspect ratio. The coolant channels are subject to a uniform as well as non-uniform, symmetric, heat flux and varying fluid properties. In the model the flow is assumed to be fully developed which is a good assumption for channels with large aspect ratios. The non-Boussinesq approximation is introduced into the integral boundary layer equations governing the system to describe the velocity and temperature distributions of the coolant in the cooling channels. The fuel plate temperature is related to the adjacent coolant fluid temperature by a fundamental law in conduction heat transfer. Water is considered as the working fluid. The results show that the present heat transfer problem encountered in nuclear research reactor such Tehran nuclear research reactor is characterized by high temperature ratios and thereby rendering the commonly applied Boussinesq approximation invalid. The non-Boussinesq results presented in the work are particularly useful for design and accident analysis of nuclear fuel during the storage cycle. ► A non-Boussinesq integral model is developed for Tehran Research Reactor. ► Numerical solution to this integral model is provided. ► The numerical solution approach exact solution asymptotically.